(untitled) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
In the wartime period, the restrictions of women become more complex as they are required to protect their families while adapting to unstable social and political conditions. Not only that, their experiences cannot be understood through gender alone, as multiple social identities often intersect and create overlapping forms of oppression. In Kristin Hannah’s The Nightingale (2015), these complexities are portrayed through Isabelle Rossignol and Vianne Mauriac, French woman who lives under German occupation during World War II and become involved in wider responsibilities with the risks imposed by the Nazi regime. This study employs Kimberlé Crenshaw’s intersectionality theory to examine how the overlapping pressures intersect with social position to create more complex situations. Then, the study applies a qualitative approach using interpretive textual analysis to investigate the meanings embedded in the characters’ actions. As they face double oppressions in the occupied country, they transform into leadership roles such as decision-makers, strategists, and collaborators. In their new role, these women can pursue resilience through personal accountability, a tactical approach, and trust-building or solidarity. Then, these leadership transformations enable them to navigate every challenge in the demands of war while carrying greater responsibilities to resilience.